Is my study cross-sectional or longitudinal? - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
The studies’ classification as cross-sectional or longitudinal constitutes one of the methodological aspects that are declared in the research projects corresponding to the specialty’s completion works. This article offers clarifying elements for the distinction between both types of studies; In this sense, it is considered that the longitudinal study’s defining essence lies in the researcher's interest in the changes over time of the investigated phenomenon.